2015
DOI: 10.1038/srep13410
|View full text |Cite
|
Sign up to set email alerts
|

Coffee consumption and risk of endometrial cancer: a dose-response meta-analysis of prospective cohort studies

Abstract: This is a dose-response (DR) meta-analysis to evaluate the association of coffee consumption on endometrial cancer (EC) risk. A total 1,534,039 participants from 13 published articles were added in this meta-analysis. The RR of total coffee consumption and EC were 0.80 (95% CI: 0.74–0.86). A stronger association between coffee intake and EC incidence was found in patients who were never treated with hormones, 0.60 (95% CI: 0.50–0.72), and subjects with a BMI ≥25 kg/m2, 0.57 (95% CI: 0.46–0.71). The overall RRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 56 publications
5
58
0
Order By: Relevance
“…Glycaemic load intake ( n = 1) met suggestive and total fat intake ( n = 1) met weak evidence. The cohort studies from the excluded meta‐analyses for coffee intake were all included in the newer meta‐analyses . The other excluded meta‐analyses also had fewer cohorts included, despite being published more recently .…”
Section: Resultsmentioning
confidence: 99%
“…Glycaemic load intake ( n = 1) met suggestive and total fat intake ( n = 1) met weak evidence. The cohort studies from the excluded meta‐analyses for coffee intake were all included in the newer meta‐analyses . The other excluded meta‐analyses also had fewer cohorts included, despite being published more recently .…”
Section: Resultsmentioning
confidence: 99%
“…The largest prospective studies that suggested an inverse relationship between coffee consumption and glioma risk used combined coffee and tea intake . The null association between coffee consumption and glioma is somewhat surprising given the previously observed inverse associations between coffee intake and other cancers and beneficial effects on cardiometabolic health; however, other studies have revealed that glioma risk factors appear to differ from those for other cancers, such as smoking …”
Section: Discussionmentioning
confidence: 96%
“…Increased consumption of tea and coffee, two of the most popular beverages worldwide, has been associated with decreased risk of cancers of several sites in human studies. [1][2][3][4][5][6][7][8][9][10] Less is known about the association between tea or coffee consumption and risk of glioma, a cancer for which few lifestyle factors have been identified. 11,12 Coffee is a rich source of caffeine, and both tea and coffee contain additional biologically active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…A maximum of 9 points was assigned to each study, 4 for selection, 2 for comparability and 3 for exposure. Scores of 0-3, 4-6 and 7-9 were regarded as low, moderate and high quality, respectively (16).…”
Section: Study Selection and Inclusion Criteriamentioning
confidence: 99%